Five-Tier Geometrical Optics Test Feasibility to Identify Misconception and the Causes in High School Students - Farah Salmadhia; Heni Rusnayati; Winny Liliawati (Berkala Ilmiah Pendidikan Fisika, 2021)
This research aimed to test the feasibility of a geometrical optics instrument to identify the misconception and its causes. The instruments used in this research were question validation sheet and five-tier geometrical optics test (FIGOT) with 14 items of questions and consisted of 48 concepts tested. FIGOT obtained from the existing four-tier test research before which was then modified by adding one more tier about the causes of misconception. FIGOT validated by six experts, in which one the aspect assessed was the suitability of the items with alternative conceptions.  The analysis of construct validity tested using CVR (almost all items have a CVRAverage value of ≥ 0.67) and the reliability was using Cronbach’s Alpha (r ≥ 0.62 for each or both tier). The identification results processed using CDQ (Confidence Discrimination Quotient). The study was conducted in two public high schools located in Bandung and two public high schools located in Jakarta with 109 students (34 males and 75 females). The result showed that most senior high school students still experienced misconceptions related to the topic of geometrical optics, 17 misconceptions from 48 concepts about geometrical optics. The biggest percentage was 81% and CPM (Confidence of Percentage Misconception) was 4,75 about plane mirror. The most dominant causes of misconception in the material of geometrical optics were due to teachers, school books, and internet. The results of the FIGOT feasibility test showed that the items of questions were possible to use to identify misconceptions and the causes of misconceptions on optical geometry.